Second Language Identity in Narratives of Study Abroad - Benson, P. author. aut Link
VIII, 179 p.
Keywords: Study abroad is now both an international industry and an experience that can have a deep impact on students' attitudes and approaches to second language learning. Narratives of Second Language Identity in Study Abroad brings together three important research areas by exploring the impact of study abroad on second language identities through narrative research. It outlines a new model of second language identity that incorporates a range of language and personal competencies. The three main dimensions of this model are explored in chapters that begin with students' study abroad narratives, followed by the authors' in-depth analysis. Further chapters use narratives to assess the impact of programme type and individual difference. Arguing that second language identity development is one of the more important outcomes of study abroad, the book concludes with recommendations on how study abroad programmes can best achieve this outcome.